Comparative Analysis of Control Strategies for Single-Phase PWM-CSCs Feeding Linear Loads: IDA-PBC, Nonlinear PI, and PI-PBC Approaches - Nivia-Vargas, Ang; Montoya Giraldo, Oscar Danilo; Gil-Gonz, Walter Juli (Statistics, Optimization & Information Computing, 2025)
This study provides an in-depth analysis and comparison of control strategies for single-phase pulse width modulation current source converters (PWM-CSCs) feeding linear loads, focusing on the implementation of interconnection and damping assignment passivity-based control (IDA-PBC), nonlinear proportional-integral (PI) control, and passivity-based PI control (PI-PBC) approaches. The dynamic characterization of PWM-CSC systems is examined through state variables, including inductor current and capacitor voltage, to model system behavior accurately. The Lyapunov stability theorem ensures the equilibrium points' global asymptotic stability, demonstrating that the proposed control techniques effectively drive system states to their desired values over time. The simulation results, conducted in a MATLAB environment, illustrate the performance of the proposed controllers. These results show that the controllers minimize total harmonic distortion (THD) while maintaining stable output current regulation. Furthermore, both IDA-PBC and PI-PBC techniques exhibit superior performance in terms of stability and signal fidelity when compared to nonlinear PI control. This study not only advances the theoretical understanding of PWM-CSC control but also offers practical insights for implementing these controllers in renewable energy systems and industrial applications. The paper concludes by proposing future research directions to further enhance control strategies for PWM-CSCs.